(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Energy is a necessity in our lives, contributing to the development of economies, and social growth. Fossil fuels such as coal, gas, and oil contribute nearly 87 of the total global energy production, whereas nuclear power plants generate approximately 6 of the energy. Renewable-energy, such as solar, geothermal, wind, hydro, and biofuels, produce the remaining 7 of the total energy demand. Photovoltaic technology (PV) is an important technology that can convert solar irradiance directly to electrical energy through a PV panel. There are advantages with the use of batteries that are used for maintaining the efficiency of power conversion chain from the PV panel to the asynchronous motor drive. Solar energy is the best option for electricity generation, as it is available everywhere, free and harmless. However, solar PV panels have drawbacks, such as very low energy conversion efficiency (less than 22.5), the high manufacturing cost of energy, and high dependence on environmental factors. The power of a PV array is unstable, and the current and voltage characteristics curve of a PV cell is non-linear at different solar irradiations, temperatures, and loads. Conventional maximum power point-tracking (MPPT) algorithms are designed for uniform environmental conditions where the P-V curve generates only one maximum power point (MPP).